Anisotropy-governed competition of magnetic phases in the honeycomb quantum magnet Na3Ni2SbO6 studied by dilatometry and high-frequency ESR - Werner, Johannes; Hergett, Waldemar; Gertig, Mario; Park, Jaena; Koo, Changhyun; Klingeler, Rüdiger (Physical review, 2017)
Thermodynamic properties and low-energy magnon excitations of S=1 honeycomb-layered Na3Ni2SbO6 have been investigated by high-resolution dilatometry, static magnetization, and high-frequency electron spin resonance studies in magnetic fields up to 16 T. At TN = 16.5 K, there is a tricritical point separating two distinct antiferromagnetic phases, AF1 and AF2, from the paramagnetic regime. In addition, our data imply short-range antiferromagnetic correlations at least up to ∼5TN. Well below TN, the magnetic field BC1≈9.5 T is needed to stabilize AF2 against AF1. The thermal expansion and magnetostriction anomalies at TN and BC1 imply significant magnetoelastic coupling, both of which are associated with a sign change of ∂L/∂B. The transition at BC1 is associated with softening of the antiferromagnetic resonance modes observed in the electron-spin-resonance spectra. The anisotropy gap Δ=360 GHz implies considerable uniaxial anisotropy. We deduce the crucial role of axial anisotropy favoring the AF1 spin structure over the AF2 one. While the magnetostriction data disprove a simple spin-flop scenario at BC1, the nature of a second transition at BC2 ≈ 13 T remains unclear. Both the sign of the magnetostriction and Grüneisen analysis suggest that the short-range correlations at high temperatures are of AF2 type.